(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2019)
The memory of anti-Jewish persecution intersected the work of prominent authors in Italian twentieth century poetry, often following oblique and unexpected trajectories that touch authors such as Montale, Sereni, Fortini, Pasolini, Saba, Levi, Quasimodo. This essay intends to probe a genealogical juncture in this poetic history, bringing into purview a series of poliperspectival models of poetic writing about the Shoah elaborated by Salvatore Quasimodo, Umberto Saba and Eugenio Montale in the early postwar years. If Quasimodo’s poesia civilepaved the way to a literary monumentalization of memory, such poetic configuration ultimately might be seen to hinge on what Friedrich Nietzsche critically termed a “spiritualization of cruelty.” Thus it was progressively identified as a potential anti-model for Italian poetry dealing with the memory of the persecution – as a reading of Montale’s treatment of this theme reveals. On the other hand, Saba condesned his afterthoughts about the “cannibalism” of racial persecution in Scorciatoie e raccontini(Shortcuts and Very Short Stories): a book of poèmes en prosethat possesses “the accent of poetry and the rigor of aphorism.” These uncanny and ironical shortcuts raise corrosive doubts about the value attached to a purported monumental memory of the Shoah and bring to attention the existence of genealogical complexity in Italian poetic writing about the Jewish genocide that calls for adequate critical recognition.